Elementary School Teachers' Understanding of Inquiry Skills and Scientific Attitude - Rif'at Shafwatul Anam; Ucu Rahayu; Mestika Sekarwinahyu; Amalis Sapriati (Al Ibtida: Jurnal Pendidikan Guru MI)
This study aims to assess elementary school teachers' inquiry skills and scientific attitudes related to science. The instrument used in this study evaluates four groups of skills: conceptualizing and planning design, implementation, analysis, interpretation, and communication. Additionally, it assesses six categories of scientific attitudes: the nature of science, the basis of science, characteristics of scientists, goals of science, benefits of science, and responses regarding scientists. This research instrument underwent validation by two experts in the field of science. Validation results using Kendall's Tau calculations showed a value of 0.853 for the inquiry ability instrument and 0.807 for scientific attitude, and both falling into the ‘very high’ category. The study involved 49 elementary school teachers. Findings revealed that teachers' inquiry skills were categorized as 'weak', indicated by an average percentage below 50% in each skill group. Regarding scientific attitude, respondents' responses varied significantly between positive and negative statements, despite similarities found in two categories: 'basic science' and 'purpose of science'. This study highlights the necessity to consider the the learning process science, particularly emphasizing the development of inquiry skills and fostering positive scientific attitudes, from elementary school through university education.